2011
DOI: 10.4161/isl.3.6.17908
|View full text |Cite
|
Sign up to set email alerts
|

Islet vs. pancreas transplantation in Brazil: Defining criteria for pancreas allocation decision

Abstract: These data reinforce the importance of the donor BMI as a defining parameter for successful islet isolation and establishes this variable as a potential pancreas allocation criterion in Brazil, where there is unequal competition for good quality organs between WOPT and PIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The study by Sá and cols. (53) reinforced the importance of the donor BMI as a defining parameter for successful islet isolation and established this variable as a potential pancreas alloca-Arch Endocrinol Metab. 2015;59/2 tion criterion for pancreatic islet transplantation in Brazil.…”
Section: Islet Transplantation and The Current Status Of This Procedumentioning
confidence: 93%
“…The study by Sá and cols. (53) reinforced the importance of the donor BMI as a defining parameter for successful islet isolation and established this variable as a potential pancreas alloca-Arch Endocrinol Metab. 2015;59/2 tion criterion for pancreatic islet transplantation in Brazil.…”
Section: Islet Transplantation and The Current Status Of This Procedumentioning
confidence: 93%
“…The effectiveness of the islet isolation procedure is given by the yield in terms of iEQs (islet equivalents based on an islet of 150 µm diameter, thereby mathematically compensating for the islet volume). In a previous study of our group [ 10 ] we adopted as a good outcome for islet isolation yields the value of 200,000 IEQs, an intermediate number when compared with those found in the literature (Lakey and cols. [ 23 ] and Kim and cols.…”
Section: Discussionmentioning
confidence: 90%
“…[ 26 ] used 300,000 IEQs as a reference for a good islet isolation outcome). In the present study, we adopted yields of 100,000 IEQs as being satisfactory because during this period only 10% of the donors offered displayed BMI > 30 kg/m 2 and our previous study showed that pancreata from donors with BMI > 30 kg/m 2 yielded an average of 277,964 IEQs, while organs from donors with BMI < 30 kg/m 2 produced 104,874 IEQs (p < 0.001) [ 10 ]. In general, 68% of the pancreas accepted by our group resulted in yields of > 100.000 iEQs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation